Research progress on classical traditional chinese medicine formula xiaoyaosan in the treatment of depression - Chen, Jianbei; Lei, Chaofang; Li, Xiaojuan; Wu, Qian; Liu, Chenyue; Ma, Qingyu; Chen, Jiaxu (Frontiers in pharmacology, 2022)
Depression is an emotional disorder that is problematic in psychiatry owing to its unclear etiology and unknown pathogenesis. Traditional Chinese medicine formulations such as Xiaoyaosan have been widely used throughout history to treat depression. In this review, we have focused on recent evidences elucidating the links between Xiaoyaosan and the treatment of depression. Data from animal and clinical studies, focusing on the pharmacological mechanisms, clinical applications, and effective materials that form the basis for the treatment of depression are presented and discussed. We found that the antidepressant effects of Xiaoyaosan are related to the effects of monoamine neurotransmitters, regulation of the hypothalamic-pituitary-adrenal axis, neuroplasticity, synaptic plasticity, inflammatory response, neuroprotection, brain-gut axis, regulation of intestinal microbiota, oxidative stress, and autophagy for reducing neuronal apoptosis. This review highlights the current evidence supporting the use of Xiaoyaosan as an antidepressant and provides an overview of the potential mechanisms involved.